2016
DOI: 10.1016/j.rasd.2015.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the impact of social problem-solving deficits on depressive vulnerability in the broader autism phenotype

Abstract: The social communication and interaction deficits associated with the autism phenotype can have serious emotional consequences for individuals on the autism spectrum. This can be particularly true during young-adulthood, a period of increased social demands and expectations. The current study investigated the specific role of social problem-solving deficits as a mediator in the relationship between autism phenotype severity and depressive symptomology in young-adults.A sample of 230 university students (48% ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 65 publications
6
23
0
Order By: Relevance
“…This research indicated there is a significant relationship between depression and broader autism phenotype in men. This result is consistent with earlier findings [7,[17][18][19]. In order to explain these findings it should be noted that some researchers believe the cause of the depression in people with HFASD is increased awareness of their deficit in interaction and communication with others [35].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This research indicated there is a significant relationship between depression and broader autism phenotype in men. This result is consistent with earlier findings [7,[17][18][19]. In order to explain these findings it should be noted that some researchers believe the cause of the depression in people with HFASD is increased awareness of their deficit in interaction and communication with others [35].…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, many depressive symptoms, including tearfulness and sadness [13], decreased self-care [14], psychomotor retardation [15], apathy, anhedonia, and loss of interest in activities [16] which are common in the general population are likely to be observed in people with comorbid ASD. The rate of depression in ASD is as high as 34 per cent [13] and the relationship between depression and autism has been confirmed in some in western studeis [7,[17][18][19]. However, a re-search showed less than 2 percent qualified for a diagnosis of major depressive disorder [20].…”
Section: Introductionmentioning
confidence: 99%
“…Findings of the current study are in consistent with Rosbrook and Whittingham (2010) [20], Zarekar et al, (2014) [35], Liew et al, (2015) [36], and Jackson and Dritschel (2016) [13]. Furthermore, Our model was statistically confirmed.…”
Section: Resultssupporting
confidence: 92%
“…Children with autism spectrum disorder (ASD) demonstrate poorer adult outcomes [Baldwin, Costley, & Warren, ; Taylor, Henninger, & Mailick, ] and well‐being across the lifespan [Barneveld, Swaab, Fagel, van Engeland, & de Sonneville, ; Ikeda, Hinckson, & Krageloh, ; Potvin, Snider, Prelock, Wood‐Dauphinee, & Kehayia, ]. Research findings also indicate that children with ASD encounter difficulty with social relationships [Orsmond, Shattuck, Cooper, Sterzing, & Anderson, ; Orsmond, Krauss, & Seltzer, ], mental health [Ratcliffe, Wong, Dossetor, & Hayes, ; Lieb & Bohnert, ; Jackson & Dritschel, ], and emotional regulation [Richey et al, ; Cai, Richdale, Uljarevic, Dissanayake, & Samson, ; Bruggink, Huisman, Vuijk, Kraaij, & Garnefski, ]. Impairments in social competence are a core feature of ASD and include deficits in social communication and social interaction [APA, ].…”
Section: Introductionmentioning
confidence: 99%